(untitled) (Progressive Agriculture, 2018)
The experiment was conducted to investigate the present status socio-economic and potentialities of buffalo production at Subornochar upazila of Noakhali district in Bangladesh. Data were collected from January to June 2014 through an interview schedule personally from 30 respondents in 6 villages of Subornochar upazila who were involved in buffalo production. All studied buffaloes were indigenous. All farmers used natural grass grown in plain land. About 7% farmers used mixed feed which was buying from local market and none used vitamin mineral supplementation. All farmers used natural breeding methods. About 40 and 67% farmers practiced vaccination and de-worming, respectively. About 27% farmers removed sick animals from healthy stock. Ninety five percent farmers allowed access to outdoor and pasturing and no farmers reared male and female buffalo separately. About 97% farmers did not keep livestock record and only 3% farmers kept their livestock record. Most of the farmers were middle aged categories (47%). Education level of farmers’ had no schooling (20%), primary (50%), secondary (20%), higher secondary (7%) and graduation (3%), respectively. The involvement of respondents in farming, business and government job were 80, 13 and 7%, respectively. Respondents used own capital, bank and NGO loan for buffalo production were 80, 13 and 7%, respectively. Lack of pasture land, technical knowledge, training facilities, unavailability fresh drinking water, higher cost for cowboy and parasitic infestation about buffalo production were 53, 80, 80, 30 ,50, and, 40%, respectively. There are great potentialities of buffalo production by improving socio-economic status in Bangladesh both for satisfying animal protein requirements and production of quality meat. Progressive Agriculture 29 (2): 158-167, 2018